Politics and Religion in Public Policy: A Review of the Alleged Hijab Ban in Paskibraka 2024 - Mudfainna; Asy'arie, Bima Fandi; Rohmah, Nisfatur; Mandaka, Dwi Arian Putra; Al Fajar, Adam Hafidz (Tebuireng: Journal of Islamic Studies and Society, 2024)
Regarding the alleged ban on wearing the hijab for female “Pasukan Pengibar Bendera Pusaka” (Paskibraka) members in 2024, political and religious relations are very important. Public policies relating to religious expression must consider human rights, including freedom of religion, recognized and protected by the Indonesian constitution. This article aims to (1) identify the government's and religious groups’ responses to these policies, (2) analyze Islamic religious law, and (3) describe the solution to the polemic in the context of Indonesian democracy. This research is library research with a qualitative approach. The discussion in this research, namely: First, this prohibition is considered to cause controversy because it is deemed to violate religious freedom and the rights of Muslim women, which causes discriminatory, contradictory attitudes and policies that are not by Pancasila. Second, the obligation to wear the hijab as written in QS. Al-Ahzab: 59, and HR. Abu Dawud., Muslim women must wear the hijab when leaving the house. This is done to cover the private parts and can help in religious observance, religious identity, and self-protection from others. Third, Some solutions to this problem are providing freedom to adhere to religion, providing a space for inclusive dialogue, providing enforcement of the principle of non-discrimination, and creating principles based on Pancasila values. So, the policies established maintain harmony, justice, and unity in the diversity of society.